Interactive course materials using multi-touch interfaces - Trinh Tuan Dung (Nanyang Technological University, 2021)
The increase in popularity of mobile devices in recent years has greatly risen the need for mobile programming. Nowadays, mobile applications can be found in various topics, from academic fields such as economics or education to ordinary services like delivery or entertainment. Applications in the education field have introduced a new educational paradigm called "Mobile Learning", which offers more freedom for learning since it allows students to study anywhere, anytime. One excellent and beneficial application of education introduced by mobile devices is interactive eBook - which does not simply provide the readers with written contents but also clear, concise and meaningful explanation. Interactive eBook is also proven to be capable of improving the reading experience and fostering the student's learning spirit. Inspired by the benefits of interactive eBook, this project aims to enhance the learning experience at NTU by converting the course materials into an interactive eBook application. Specifically, this project uses the course material of the course CZ2004 Human - Computer Interaction, but the ultimate goal is to make it applicable to all courses in NTU. The interactive eBook application is implemented using React Native, a cross-platform mobile application framework created by Facebook.